2002
DOI: 10.1039/b007741k
|View full text |Cite
|
Sign up to set email alerts
|

Amaryllidaceae, Sceletium, imidazole, oxazole, thiazole, peptide and miscellaneous alkaloids

Abstract: This review covers alkaloids classified in the plant families Amaryallidaceae and Sceletium. In addition alkaloids possessing imidazole, oxazole and thiazole structures are listed followed by alkaloids possessing peptide linkages. Finally miscellaneous alkaloids include those compounds found naturally which cannot be classified into known groups; a relative Pandora's box. A total of 620 structures has been reviewed from 218 references found in the literature for the period July 1999 to June 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 340 publications
(144 reference statements)
0
30
0
Order By: Relevance
“…The isolated haemanthamine (10 mg) was found to be pure by LC-MS analysis. 1 H NMR spectrum of haemanthamine was recorded in CDCl 3 on a Varian Gemini (200 MHz) NMR spectrometer, using TMS as the internal standard. The chemical shift is expressed in δ (ppm) and J in Hz: 1H, s, Ar).…”
Section: Preparative Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated haemanthamine (10 mg) was found to be pure by LC-MS analysis. 1 H NMR spectrum of haemanthamine was recorded in CDCl 3 on a Varian Gemini (200 MHz) NMR spectrometer, using TMS as the internal standard. The chemical shift is expressed in δ (ppm) and J in Hz: 1H, s, Ar).…”
Section: Preparative Extractionmentioning
confidence: 99%
“…In the recent years attention has been focused on the biological activity of several Amaryllidaceae alkaloids [1] which displayed antimalarial [2,3], antiviral [4,5] and antiproliferative activity [6]; the most important Amaryllidaceae alkaloid is undoubtedly galanthamine that is approved for the pharmacological treatment of Alzheimer's disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the optically active heterocyclic compounds have been successfully used in asymmetric synthesis as chiral templates [4,5] or ligands [6][7][8][9] reported the synthesis of thioethers and thioesters in acetonitrile. Herein, we reported an efficient synthesis of some thiazoline and thiazine multithioethers in a friendly solvent-ethanol and explored the biological activities of the obtained target products against A549 (human lung cancer cell) and Bcap-37 (human breast cancer cell).…”
Section: Introductionmentioning
confidence: 99%
“…The extreme limits of the electron density observed in DMOZ is À4.824eÀ2 (red) and 4.824eÀ2 (blue), where blue indicates the strongest attraction and red indicates the strongest repulsion. The negative (red and yellow) regions of MEP were related to electrophilic reactivity and the 1 For interpretation of color in Fig. 7, the reader is referred to the web version of this article.…”
Section: Molecular Electrostatic Potential (Mep)mentioning
confidence: 99%
“…Besides, additional functionalities can readily be introduced into 2-oxazolines via functional monomers units and these compounds fulfil fundamental requirements for an application as carrier molecules in radionuclide therapy. Recent studies have shown that highly active sugar oxazoline act as donor substrates for transglycosylation and exhibit potent anti-HIV activity [1][2][3][4][5]. Oxazoline analogues have also been shown to induce cell growth inhibition, apoptosis, and microtubule disruption without alkylating beta-tubulin [6].…”
Section: Introductionmentioning
confidence: 98%